Studies on the Anti-Inflammatory Effect and Its Mechanisms of Sophoridine. (9th April 2014) - Huang, Xiumei; Li, Bo; Shen, Lianzhong
Abstract : This work is to study the anti-inflammatory effect and its mechanisms of sophoridine in vitro and in vivo. For this aim, the influences of sophoridine on several inflammatory mediators were investigated. Excessive inflammatory response in vitro model was developed by using lipopolysaccharide (LPS) to stimulate the mouse peritoneal macrophages and HL-60 cells to produce IL-6 and IL-8. Carrageenin-induced mouse paw edema model was used as inflammatory response in vivo model. MTT method, ultraviolet spectrophotometric method, and radioimmunoassay were used to measure the changes of TNF α, IL-6, PGE2, and IL-8 in in vitro cell culture supernatant or in the local inflammatory exudates. The results showed that sophoridine inhibited the production of IL-8 in in vitro cell culture supernatant and inhibited the production of TNF α, PGE2, and IL-8 in the local inflammatory exudates but had no significant effects on the production of IL-6 in vitro and in vivo. It is demonstrated that sophoridine's anti-inflammatory effect was due to its ability to inhibit the production of cytokine and inflammatory mediators.